Overexpression of C1orf74 predicts poor outcome and promote cervical cancer progression - Hai Zhu; Yaping Wang; Yu Zhang; Yun Tian; Duan Liu; Xiabing Li; Gaili Ji; Caixia Ma; Hongyu Li (Heliyon, 2024)
Cervical cancer (CC), which ranks among the four most common cancers in women, is a leading cause of both illness and death globally. It's urgent to identify a new biomarker to elucidate the potential mechanisms underlying the progression of CC. Here, we screened the differentially expressed genes (DEGs) in the Cancer Genome Atlas database (TCGA) and selected Chromosome 1 open reading frame 74 (C1orf74) for further investigation. C1orf74 levels were elevated, indicating a link to poor prognosis.Higher expression of C1orf74 was significantly related to clinical stage, T stage, histological type and survival status. Functional enrichment analysis indicated that C1orf74 is likely associated with the MAPK signaling pathway. Moreover, we found that C1orf74 was correlated with multifarious immune cell infiltration. Finally, the knockdown of C1orf74 significantly inhibited the growth of CC in vitro. In conclusion, C1orf74 promotes CC proliferation and progression, is closely associated with poor prognosis, and plays a role in the tumor immune microenvironment. The research indicates that C1orf74 is important for treating CC and may help develop new strategies to improve patient outcomes.